A novel immunodominant CD8+ T cell response restricted by a common HLA-C allele targets a conserved region of Gag HIV-1 clade CRF01_AE infected thais - Buranapraditkun, S; Hempel, U; Pitakpolrat, P; Allgaier, R; Thantivorasit, P; Lorenzen, S; Sirivichayakul, S; Hildebrand, W; Altfeld, M; Brander, C; Walker, B; Phanuphak, P; et al. (2011)
Background: CD8+ T cell responses play an important role in the control of HIV-1. The extensive sequence diversity of HIV-1 represents a critical hurdle to developing an effective HIV-1 vaccine, and it is likely that regional-specific vaccine strains will be required to overcome the diversity of the different HIV-1 clades distributed world-wide. Unfortunately, little is known about the CD8+ T cell responses against CRF01_AE, which is responsible for the majority of infections in Southeast Asia. Methodology/Principal Findings: To identify dominant CD8+ T cell responses recognized in HIV-1 clade CRF01_AE infected subjects we drew upon data from an immunological screen of 100 HIV-1 clade CRF01_AE infected subjects using IFN-gamma ELISpot to characterize a novel immunodominant CD8+ T cell response in HIV-1 Gag restricted by HLA-Cw*0102 (p24, 277YSPVSILDI 285, YI9). Over 75% of Cw*0102+ve subjects targeted this epitope, representing the strongest response in more than a third of these individuals. This novel CD8 epitope was located in a highly conserved region of HIV-1 Gag known to contain immunodominant CD8 epitopes, which are restricted by HLA-B*57 and -B*27 in clade B infection. Nonetheless, viral escape in this epitope was frequently observed in Cw*0102+ve subjects, suggestive of strong selection pressure being exerted by this common CD8+ T cell response. Conclusions/Significance: As HLA-Cw*0102 is frequently expressed in the Thai population (allelic frequency of 16.8%), this immunodominant Cw*0102-restricted Gag epitope may represent an attractive candidate for vaccines specific to CRF01_AE and may help facilitate further studies of immunopathogenesis in this understudied HIV-1 clade. © 2011 Buranapraditkun et al.